Current concepts on osteonecrosis of the femoral head - Moya-Angeler, Joaquin (World J Orthop, 2015)
It is estimated that 20000 to 30000 new patients are diagnosed with osteonecrosis annually accounting for approximately 10% of the 250000 total hip arthroplasties done annually in the United States. The lack of level 1 evidence in the literature makes it difficult to identify optimal treatment protocols to manage patients with pre-collapse avascular necrosis of the femoral head, and early intervention prior to collapse is critical to successful outcomes in joint preserving procedures. There have been a variety of traumatic and atraumatic factors that have been identified as risk factors for osteonecrosis, but the etiology and pathogenesis still remains unclear. Current osteonecrosis diagnosis is dependent upon plain anteroposterior and frog-leg lateral radiographs of the hip, followed by magnetic resonance imaging (MRI). Generally, the first radiographic changes seen by radiograph will be cystic and sclerotic changes in the femoral head. Although the diagnosis may be made by radiograph, plain radiographs are generally insufficient for early diagnosis, therefore MRI is considered the most accurate benchmark. Treatment options include pharmacologic agents such as bisphosphonates and statins, biophysical treatments, as well as joint-preserving and joint-replacing surgeries. the surgical treatment of osteonecrosis of the femoral head can be divided into two major branches: femoral head sparing procedures (FHSP) and femoral head replacement procedures (FHRP). In general, FHSP are indicated at pre-collapse stages with minimal symptoms whereas FHRP are preferred at post-collapse symptomatic stages. It is difficult to know whether any treatment modality changes the natural history of core decompression since the true natural history of core decompression has not been delineated.